Prospective study of the UGT1A1*27 gene polymorphism during irinotecan therapy in patients with lung cancer: Results of Lung Oncology Group in Kyusyu (LOGIK1004B). Issue 4 (11th May 2016) - Fukuda, Minoru; Suetsugu, Takayuki; Shimada, Midori; Kitazaki, Takeshi; Hashiguchi, Kohji; Kishimoto, Junji; Harada, Taishi; Seto, Takashi; Ebi, Noriyuki; Takayama, Koichi; Sugio, Kenji; Semba, Hiroshi; et al.
Abstract : Background: Uridine 5′‐diphospho‐glucuronosyltransferase 1A1 ( UGT1A1*27 ) is known to impair the effect of UGT in basic research; however, little clinical investigation has been conducted. To evaluate the effect of the UGT1A1*27 polymorphism in irinotecan therapy, we conducted a prospective study. Methods: Eligibility criteria included: lung cancer patients; scheduled irinotecan therapy doses of single ≥ 80, combination ≥ 50, radiation with single ≥ 50, or radiation with combination ≥ 40 mg/m 2 ; age ≥ 20; and Eastern Cooperative Oncology Group performance score (PS) 0–2. Patients were examined for UGT1A1*28 and *6 polymorphisms and received irinotecan. When the UGT1A1*28 polymorphism was detected, a search for UGT1A1*27 was conducted. Fifty patients were enrolled, with 48 patients determined eligible. Results: UGT1A1 polymorphisms *28/*28, *6/*6, *28/*6, *28/−, *6/−, −/− observed 0 (0%), 1 (2%), 1 (2%), 7 (15%), 17 (35%) and 22 (46%), respectively. UGT1A1*27 were examined in nine patients including one ineligible patient; however, no polymorphisms were found. The study ceased after interim analysis. In an evaluation of the side effects of irinotecan, patients with UGT1A1*28 and UGT1A1*6 polymorphisms had a higher tendency to experience febrile neutropenia than wild type (25% and 32% vs. 14%). Incidences of grade 3/4 leukopenia and neutropenia were significantly higher in patients with UGT1A1*28 polymorphisms compared with wild type (75% vs. 32%, P = 0.049; 75% vs. 36%, P = 0.039, respectively). Conclusion: Our prospective study did not locate the UGT1A1*27 polymorphism, suggesting that UGT1A1*27 does not significantly predict severe irinotecan toxicity in cancer patients.